CORAK TEOLOGI DAN PRINSIP SOSIAL-KEAGAMAAN PADA LEKTUR KEAGAMAAN DI PONDOK PESANTREN HUSNUL KHOTIMAH DAN BINA'UL UMMAH KUNINGAN JAWA BARAT - SAEFULLAH, ASEP (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2012)
This article tries to study the kinds, study areas, and discourse of religious literatures in the pesantrens of Husnul Khotimah and Binaul Ummah, Kuningan Jawa Barat; to know religious discourse, especially in the areas of akidah (faith) and akhlak (morals); and to recognize the characteristics of religious theology of the pesantrens as well as the socio-religious doctrines developed in both of these pesantrens. This research is a field research. The methods of data collecting used in this research are literature study, documentation, interoiew, and participant obseroation. The characterstics of theology which are easily recognized in the the Pesantren of Husnul Khotimah and Binaul Ummah are the theology based on Asy'ariyah and Hanbali characteristics. Based on the moral (akhlak) aspect, both of these pesantrens rely it on some of Hasan Al-Bann as views, especially in the book of Rukn al-'Amal au Manhajal-Islah al-Islami Ii al-Fard wa alMujtama: i.e. the characters of Muslim generation as follow: 1) Quwwah al-Jism, 2) Matanah al-Khulq, 3) Saqafah al-Fikr, 4) al-Qudrah 'ala al-Kasb, 5) Salamah al-'Aqidah, 6) Sihhah al- 'Ibadah, 7) Mujahadah al-Nafs, 8) al-Hirs 'ala al-Waqt, 9) AI-Nizam fi Syu’un killiha, 10) al-Nafu Ii al-Gair Key Words: Theology, Religious Literatures, Pesantren, Jawa Barat